Efficacy of Trimethoprim-Sulfamethoxazole in Combination with an Echinocandin as a First-Line Treatment Option for Pneumocystis Pneumonia: A Systematic Review and Meta-Analysis - Hideo Kato; Mao Hagihara; Nobuhiro Asai; Takumi Umemura; Yuichi Shibata; Jun Hirai; Yuka Yamagishi; Takuya Iwamoto; Hiroshige Mikamo (MDPI AG, 2022)
Although combination therapy using trimethoprim-sulfamethoxazole (TMP-SMX) plus echinocandins has been reported to reduce the mortality of patients with pneumocystis pneumonia (PCP), it remains unclear whether it is more effective than TMP-SMX monotherapy, the current first-line treatment for this disease. Hence, we performed a systematic review and meta-analysis to compare the efficacies of these treatment options for PCP. The Scopus, EMBASE, PubMed, CINAHL, and Ichushi databases were searched for studies (up to January 2022) reporting the mortality and positive response rates (fewer clinical symptoms, improved partial pressure of arterial oxygen, and resolution of pneumonitis on chest imaging) of PCP patients receiving monotherapy or combination therapy. Four studies met the inclusion criteria. All four presented mortality data and one had positive response rates. Compared with the monotherapy, the combination therapy resulted in significantly lower mortality and higher positive response rates (mortality: odds ratio (OR) 2.20, 95% confidence interval (CI) 1.46-3.31; positive response rate: OR 2.13, 95%CI 1.41-3.23), suggesting it to be an effective and promising first-line therapy for PCP. However, further safety evaluations are needed to establish this as a fact.